Effect of short-term ingestion of the methanolic extract of mitragyna speciosa on sperm quality in mice - Mat Daud, Mohamad Syamsudin; Shaik Mossadeq, Wan Mastura; Abdul Kadir, Arifah; Nor Hussein, Fuzina (2011)
Mitragyna speciosa (MS) which is known as “Ketum” in Malaysia and “Kratom” in Thailand is a tropical plant indigenous to Southeast Asia. The leaves of MS have been used by natives of these countries for their opium-like effects and cocaine-like stimulant activities to overcome fatigue, enhance tolerance to hard work, prolong the duration of sexual intercouse and increase libido in males. However, no scientific studies have been carries out to assess the effects of MS consumption on the quality of sperm in animals or man. In this study, the effect of short-term ingestion of MS on the quality of sperm in mice was investigated. Forty mice were divided into 5 groups; 2 controls and 3 treatments. The negative control group received 0.9% sodium chloride (NaC1, 10 mL/ kg) while the positive control received clomiphene (25 mg/70 kg). the respective treatment groups received either 50, 100 and 200 mg/kg of MS extract. The drugs and extracts were administered orally once daily for 14. The results showed an increase in the number of sperms in groups treated with MS. The morbidity rates of the sperm in groups treated with MS were markedly lower than that of the control groups. In addition, marked deformity in the sperm in the form of swelling at the tail was observed in the groups treated with MS. In conclusion, mice treated with MS showed an increase in the number of sperm count in spite of defect in sperm morphology and reduced sperm motility.